A STYLISTIC ANALYSIS OF ADVERTISING DISCOURSE: A CASE STUDY OF COKE COMMERCIAL ADVERTISEMENT - Desi Rahma Yuni Br.Sinulingga (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
This study attempts to examine the many linguistic idioms employed in English-language commercial and coke advertisements on the internet. By gathering five coke advertisements from the internet and using them as documentation, this research employed a qualitative descriptive methodology. Data condensing, data visualization, and conclusion/verification drawing are some of the data analysis techniques employed. As a result of this research, the researcher discovered three language styles used in analyzing the data: comparison, problem solution, hard sell, soft sell, lecture and drama, straightforward style, demonstration, and slice of life. The researchers also discovered three language styles used in coke product advertisements comparison, problem solution, hard sell.